Peranan kreativitas dalam memperkuat pendekatan deep learning pada pembelajaran sekolah dasar - Nurhamidah Nasution; Neviyarni (Karoteh Utama, 2025)
This study aims to examine the role of creativity in strengthening the deep learning approach in elementary school learning through a systematic review of national and international literature. The method employed was a Systematic Literature Review (SLR) guided by the PRISMA framework, encompassing the stages of literature search, selection, and synthesis of findings from 25 relevant articles. The results indicate that creativity plays a significant role in fostering deep conceptual understanding, enhancing critical thinking skills, and encouraging students to connect, explore, and reflect on concepts in a meaningful way. Various instructional strategies, including project-based learning, the STEAM approach, inquiry-based learning, science experiments, art-based activities, and open-ended tasks, have been shown to effectively promote creativity while simultaneously strengthening deep learning processes. However, the implementation of these approaches remains challenged by several factors, such as limited teacher competence, curriculum pressures, inadequate learning facilities, and a lack of professional development in creative pedagogy. Overall, the integration of creativity and deep learning is considered a relevant and strategic approach to improving the quality of elementary education and preparing students to meet the demands of 21st-century skills.